(untitled) (Delta Medical College Journal, 2018)
Intrauterine demise of one of the twin fetuses during second or third trimester of pregnancy is an uncommon complication. Fetal death of a twin during the first trimester is not an uncommon event and does not appear to impair the development of the second twin. However, fetal death during second or third trimester may increase the risk of IUGR, microcephaly, cerebral encephalomalacia, pre eclampsia, preterm labour, perinatal mortality. We present two cases with single fetal demise. Death of one of the two fetuses occurred at 23 weeks of gestation in the first case and at 33 weeks in the second case. Both patients were managed conservatively with close fetal monitoring and serial assessment of mother’s clotting profile. Cesarean section was done especially due to patients’ interest at 34 weeks and 35 weeks respectively. A fetus papyraceous was found in the first case. Both the cases were dichorionic diamniotic pregnancies with no maternal and fetal complications during pregnancy or the post partum period. Delta Med Col J. Jan 2018 6(1): 53-57